2011
DOI: 10.5216/pat.v41i4.15100
|View full text |Cite
|
Sign up to set email alerts
|

TRATAMENTOS PARA A SUPERAÇÃO DE DORMÊNCIA EM SEMENTES DE Brachiaria humidicola (Rendle) Schweick

Abstract: Villas Bôas 4 INTRODUÇÃO O Brasil é o maior produtor, consumidor e exportador de sementes de espécies forrageiras tropicais, com produção estimada de 70 mil toneladas, na safra 2008/2009 (Abrasem 2010), já tendo alcançado produções superiores a 100 mil toneladas, em safras anteriores. Mais de 80% do mercado é dominado por cultivares do gênero Brachiaria, cuja introdução ABSTRACT RESUMO na formação de pastagens, no Cerrado, resultou em ganhos significativos nos índices de produtividade de carne, devido ao rápid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 4 publications
0
14
0
5
Order By: Relevance
“…Means followed by the same lowercase letter on the line, and capitalized on the column; do not differ statistically by the Tukey's test at 5% probability. Costa et al (2011) found that storage for 21 months was more effective for overcoming B. humidicola seed dormancy than acid scarification or germination promoting substances *There was no interaction between harvests and treatments for this variable. Means followed by the same lowercase letter on the line, and capitalized on the column; do not differ statistically by the Tukey's test at 5% probability.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Means followed by the same lowercase letter on the line, and capitalized on the column; do not differ statistically by the Tukey's test at 5% probability. Costa et al (2011) found that storage for 21 months was more effective for overcoming B. humidicola seed dormancy than acid scarification or germination promoting substances *There was no interaction between harvests and treatments for this variable. Means followed by the same lowercase letter on the line, and capitalized on the column; do not differ statistically by the Tukey's test at 5% probability.…”
Section: Resultsmentioning
confidence: 91%
“…application. However, seeds stored for periods longer than 12 months may have lower quality and treatments with sulfuric acid does not promote germination increase, as evidenced by Custódio et al (2012), in B. brizantha seeds lots. Paniago et al (2014) found that the storage time did not provide B. humidicola seed quality increase nor reduced the percentage of dormant seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the agronomic advantages, the seeds of this hybrid species, as well as the other Brachiarias, present dormancy (Costa et al, 2011). However, the dormancy mechanism has peculiarities for different species, making it difficult to generalize about its causes, which may occur independently or in combination, as is the case for most seeds of forage grasses (Previero et al, 1998, Santos et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a partially problem for seed production, dormancy soon after harvest makes the evaluation of the physiological quality and the implementation of measures related to quality control of production difficult, which requires appropriate methods to break the dormancy of seeds. Furthermore, it is known that, for many forage species, the effectiveness of methods designed to break dormancy varies depending on the age of the seeds (Costa et al, 2011) and that the storage itself is enough to promote dormancy breaking.…”
Section: Introductionmentioning
confidence: 99%